2022
DOI: 10.1039/d2ra06220h
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon from almond shells using an eco-compatible method: screening, optimization, characterization, and adsorption performance testing

Abstract: Screening and optimization by DOE, an ecofriendly method under vacuum for the preparation of activated carbon from almond shells, characterization, and application for textile wastewater treatment are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The mixture thus obtained is filtered and dried at 80 °C. Ag-ZnO/CA composite is prepared by an intimate mixture of ZnO and activated carbon (AC) from almond shells previously developed [17]. The mixture is then impregnated with a solution of AgNO3, the precipitate is filtered and dried in the same way as Ag-ZnO.…”
Section: Synthesis Of Photocatalytic Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture thus obtained is filtered and dried at 80 °C. Ag-ZnO/CA composite is prepared by an intimate mixture of ZnO and activated carbon (AC) from almond shells previously developed [17]. The mixture is then impregnated with a solution of AgNO3, the precipitate is filtered and dried in the same way as Ag-ZnO.…”
Section: Synthesis Of Photocatalytic Compositesmentioning
confidence: 99%
“…4). These values mean that the composites particles are positively charged in the solution with pH values below the zero-point charge and negatively charged at pH values above the isoelectric point charge [17,30]. The evolution of a zeta potential of CA varies positively as a function of pH this indicates a neutrality of charge on their surface.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Hidayu et al [34] prepared activated carbon from palm kernel shell by chemical activation to absorb β-carotene in crude palm oil and showed that activation of palm kernel shell carbon using zinc chloride (ZnCl2) with mass saturation ratio 1:1 for 24 hours and carbonization at 500°C for 90 minutes shows the highest percentage of β-carotene removal (69%). Boulika et al [35] synthesized activated carbon from almond shell using H3PO4 as a chemical activator and room vacuum decomposition as a physical activator. They studied the optimum adsorption e ciency of crystal violet dye on the produced activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…and their elimination from the environment has become a top priority. For the treatment of industrial effluents, a number of physicochemical processes have been used, including adsorption [4,5], coagulation flocculation, membrane filtration [6]. However, all of these methods, with the exception of the adsorption method, cannot be used in an industrial setting due to their high cost.…”
Section: Introductionmentioning
confidence: 99%